Composite solid electrolyte for lithium secondary battery and method for producing same

The method of using UV-curable polymers and ceramic compounds to produce a composite solid electrolyte with improved ionic conductivity addresses the challenge of non-uniform dispersion in conventional composite solid electrolytes, resulting in enhanced lithium ion conduction.

JP2025511493AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024553210
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-05-31
Filing Date
2023-05-31
Publication Date
2025-04-16
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

Conventional composite solid electrolytes for lithium secondary batteries face challenges in achieving uniform dispersion of inorganic substances within the polymer solution, leading to non-uniform particle distribution and low ionic conductivity.

Method used

A method involving the use of UV-curable polymers and ceramic compounds, where a solution is coated on a substrate, irradiated with UV rays to cure, and then sintered to produce a ceramic ion conductor, which is subsequently immersed in a solution containing a second polymer and lithium salt to enhance ionic conductivity.

Benefits of technology

This approach results in a composite solid electrolyte with improved ionic conductivity, allowing for the formation of a cross-linked structure that enhances the ion conduction path for lithium ions, thereby overcoming the limitations of conventional manufacturing techniques.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511493000001
    Figure 2025511493000001
  • Figure 2025511493000002
    Figure 2025511493000002
  • Figure 2025511493000003
    Figure 2025511493000003
Patent Text Reader

Abstract

The present specification relates to a composite solid electrolyte for a lithium secondary battery and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0067022 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070203 filed on May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.

[0002] The present invention relates to a composite solid electrolyte for a lithium secondary battery and a method for producing the same. [Background technology]

[0003] Lithium-ion batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, and if the separator is damaged due to deformation or external impact, a short circuit may occur, which may lead to the risk of overheating or explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium-ion secondary batteries is a very important issue.

[0004] Lithium secondary batteries using solid electrolytes have the advantages of increased safety and the prevention of electrolyte leakage, improving battery reliability, and facilitating the production of thin batteries. In addition, because lithium metal can be used in the negative electrode, the energy density can be improved, and as a result, they are expected to be used in small secondary batteries as well as high-capacity secondary batteries for electric vehicles, and are attracting attention as next-generation batteries.

[0005] Among solid electrolytes, polymer solid electrolytes may use polymer materials having ion conductivity or inorganic materials such as oxides or sulfides having ion conductivity. Composite solid electrolytes that combine polymer materials and inorganic materials have also been proposed.

[0006] Such conventional composite solid electrolytes are manufactured by preparing a solution or slurry in which a polymer and an inorganic material are mixed and dispersed, and then solution casting the solution onto a substrate and drying the solution at a high temperature. However, the conventional composite solid electrolyte manufacturing technology has a limitation in that the inorganic material is not uniformly dispersed in the polymer solution, resulting in non-uniform inorganic particle distribution in the composite solid electrolyte, making it difficult to manufacture a composite solid electrolyte with improved ionic conductivity.

[0007] In order to overcome these limitations of conventional composite solid electrolytes, there is a need to develop a technology that can uniformly disperse polymers and inorganic materials and improve the ionic conductivity of a composite solid electrolyte including the same. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 2017-0045011 Summary of the Invention [Problem to be solved by the invention]

[0009] It is an object of the present invention to provide a composite solid electrolyte with improved ionic conductivity.

[0010] It is another object of the present invention to provide a method for preparing a composite solid electrolyte having improved ionic conductivity.

[0011] Another object of the present invention is to provide an all-solid-state battery including a composite solid electrolyte with improved ionic conductivity. [Means for solving the problem]

[0012] In order to achieve the above object, the present invention provides a method for producing a composite solid electrolyte for a lithium secondary battery, the method comprising: (S1) applying a composite solid electrolyte-forming solution, including a first polymer, which is a UV-curable polymer, and a ceramic compound, onto a substrate to form a coating film; (S2) irradiating the coating film with ultraviolet (UV) light and curing the same to produce a first composite; (S3) sintering the first composite to produce a ceramic ion conductor; and (S4) immersing the ceramic ion conductor in a solution including a second polymer and a lithium salt, and curing the solution to produce a second composite.

[0013] The present invention also provides a composite solid electrolyte for a lithium secondary battery, comprising: a ceramic ion conductor comprising a ceramic compound; a second polymer; and a lithium salt, wherein the ceramic ion conductor comprises a cross-linked structure comprising the ceramic compound.

[0014] The present invention also provides an all-solid-state battery including the composite solid electrolyte for lithium secondary batteries. Effect of the Invention

[0015] The composite solid electrolyte according to the present invention can effectively improve the ion conduction of lithium ions by forming a ceramic ion conductor using a first polymer, which is a UV-curable polymer, and a ceramic compound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will now be described in further detail to aid in the understanding of the present invention.

[0017] The terms and words used in this specification and the claims should not be interpreted in a limited manner based on their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.

[0018] Method for producing composite solid electrolyte for lithium secondary battery A method for preparing a composite solid electrolyte according to an embodiment of the present invention may include the following steps: (S1) applying a solution for forming a composite solid electrolyte, the solution including a first polymer, which is a UV-curable polymer, and a ceramic compound, onto a substrate to form a coating film; (S2) irradiating the coating film with ultraviolet (UV) light and curing the coating film to produce a first composite; (S3) sintering the first composite to produce a ceramic ion conductor; (S4) immersing the ceramic ion conductor in a solution containing a second polymer and a lithium salt and curing the solution to produce a second composite.

[0019] Conventional composite solid electrolytes are manufactured by coating or dispersing a solution or slurry of a mixture of polymer and inorganic material on a substrate using a method such as solution casting, and then drying the coated solution or slurry. However, this method has a problem in that the ionic conductivity of the solid electrolyte is not improved due to non-uniform dispersion and precipitation of the inorganic material in the polymer solution.

[0020] To improve this, the present inventors have completed a composite solid electrolyte having improved ionic conductivity by uniformly dispersing particles of the ceramic compound in a ceramic ion conductor manufactured using a first polymer, which is a UV-curable polymer, and a ceramic compound.

[0021] In the method for producing the composite solid electrolyte, a solution containing a first polymer, which is a UV-curable polymer, and a ceramic compound is irradiated with ultraviolet light and then cured to produce a first composite, whereby the ceramic compound can be uniformly dispersed in the first polymer solution. By producing a ceramic ion conductor in which the ceramic compound particles are uniformly dispersed, the ionic conductivity of lithium ions can be improved, and a composite solid electrolyte with improved ionic conductivity can be produced.

[0022] Hereinafter, each step of the method for preparing the composite solid electrolyte according to the present invention will be described in detail.

[0023] In the present invention, in the step (S1), a composite solid electrolyte forming solution including a first polymer, which is a UV curable polymer, and a ceramic compound may be coated on a substrate to form a coating film.

[0024] The first polymer may be a UV-curable polymer. The UV-curable polymer refers to a polymer that forms a photo-crosslinked bond using ultraviolet (UV) rays. When the UV-curable polymer is irradiated with ultraviolet (UV) rays in the presence of a photoinitiator, a photopolymerization reaction is initiated to form a photo-crosslinked bond. Therefore, the UV-curable polymer may have a physical property that shows a maximum absorbance in at least a part of a wavelength region or the entire region of the ultraviolet (e.g., wavelengths of 300 nm to 400 nm) region in an absorbance spectrum with respect to wavelength.

[0025] The first polymer may include at least one selected from the group consisting of polyisocyanurate (PIR), epoxy, polyurethane, polyacrylate, and poly(methyl methacrylate) (PMMA).

[0026] In the polyacrylate, examples of the UV-curable acrylate monomer include hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), ethylene glycol diacrylate (EGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylated triacrylate (TMPEOTA), glycerol propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETA), and dipentaerythritol hexaacrylate (DPHA), but are not limited thereto. Any acrylate monomer commonly used in the art may be used without particular limitation.

[0027] The composite solid electrolyte forming solution may further include a photopolymerization initiator. Examples of the photopolymerization initiator include, but are not limited to, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]2-methyl-1-propanone, methylbenzoyl formate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4[(methylthio)phenyl]-2(4-morpholinyl)-1-propanonediphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, the photopolymerization initiator may be, as currently available commercially, Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Esacure KIP 100F, etc. The photopolymerization initiator may be used alone or in combination of two or more different types.

[0028] The content of the photoinitiator may be 1.0 to 5.0 wt% based on the content of the first polymer. If the content of the photoinitiator is less than 1.0 wt% or more than 5.0 wt% based on the content of the first polymer, crosslinking between the first polymer and the ceramic compound may not be formed, making it difficult to form a crosslinked film.

[0029] The ceramic compound may be an oxide-based or phosphate-based solid electrolyte. The oxide-based or phosphate-based solid electrolyte may be a garnet-type lithium-lanthanum-zirconium oxide (LLZO, Li7La3Zr2O 12 ), perovskite-type lithium-lanthanum-titanium oxide (LLTO, Li 3x La 2 / 3-xTiO3), phosphate-based NASICON-type lithium-aluminum-titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO4)3), lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 The oxide- or phosphate-based solid electrolytes have a very high grain boundary resistance, and therefore require a sintering process at 1000°C or higher. This causes problems such as lithium volatilization at high temperatures, phase transition, and impurity phase formation. However, oxide- or phosphate-based solid electrolytes generally have a maximum sintering temperature of 10 -4 ~10 -3 It has the advantages of having an ionic conductivity value of 100 S / cm, being stable in a high voltage region, being stable in air, and being easy to synthesize and handle.

[0030] Therefore, the first polymer according to the present invention can be mixed with a different material to prepare a hybrid solid electrolyte, thereby making it possible to compensate for the shortcomings of each material.

[0031] The oxide-based or phosphate-based solid electrolyte has high high-temperature stability since it does not easily burn or ignite even under high-temperature conditions of 400° C. or more. Therefore, when the ceramic ion conductor includes the oxide-based or phosphate-based solid electrolyte, it can improve the mechanical strength as well as the high-temperature stability and ionic conductivity of the composite solid electrolyte for a lithium secondary battery.

[0032] The substrate is not particularly limited as long as it can serve as a support on which the composite solid electrolyte-forming solution is applied, and may be, for example, stainless steel (SS), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.

[0033] The coating method is also not particularly limited as long as it can coat the composite solid electrolyte-forming solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.

[0034] In the present invention, in the step (S2), the coating film may be irradiated with ultraviolet (UV) light and then cured to produce a first composite body.

[0035] Conventional composite solid electrolytes are prepared by mixing and dispersing a polymer and an inorganic material to prepare a solution, coating the solution on a substrate using a method such as solution casting, and then drying the solution to prepare a final composite solid electrolyte film. However, such composite solid electrolytes have problems in that the inorganic material is not uniformly dispersed in the polymer solution, resulting in non-uniform inorganic particle distribution in the final composite solid electrolyte film, resulting in low ion conductivity and long manufacturing time.

[0036] Therefore, the present inventors have completed a composite solid electrolyte having improved ionic conductivity by using the first polymer, which is a UV-curable polymer, and curing it in a short time so that the ceramic compound particles are uniformly dispersed in the first composite.

[0037] The wavelength of the ultraviolet (UV) rays used in the curing reaction may be 200 to 400 nm.

[0038] In the first composite, the ceramic compound may be included in an amount of 1 part by weight or more to less than 10 parts by weight per part by weight of the first polymer. More specifically, the weight ratio of the first polymer and the ceramic compound may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9. If the ceramic compound is included in an amount of less than 1 part by weight per part by weight of the first polymer, the connection between the ceramic compounds is not smoothly performed after the sintering process in the following step (S4), and it is difficult to form a ceramic ion conductor having a cross-linked structure, and the mechanical properties are also weak, so that it is easily broken or destroyed, and it is difficult to manufacture a composite solid electrolyte. In addition, if the ceramic compound is included in an amount of more than 10 parts by weight per part by weight of the first polymer, the ceramic compound particles are not uniformly dispersed in the first polymer, and a phenomenon occurs in which the ceramic compound particles aggregate with each other, and phase separation occurs between the first polymer and the aggregated ceramic compound particles, resulting in a composite solid electrolyte having reduced ion conductivity.

[0039] In the present invention, in the step (S3), the first composite body may be sintered to prepare a ceramic ion conductor.

[0040] As used herein, sintering refers to the process of subjecting the first composite to sufficient temperature and pressure to form it into a harder mass of particles.

[0041] The ceramic ion conductor may be prepared by sintering the first composite body, pyrolyzing the first polymer component, and sintering the remaining ceramic compound particles.

[0042] Through the sintering process, the first polymer acts as a support to allow the ceramic compound particles to be connected to each other, and the ceramic compound particles are connected to each other to form a ceramic ion conductor having a cross-linked structure.

[0043] The ceramic ion conductor may serve to form an ion conduction path for lithium ions.

[0044] The sintering can be performed by appropriately selecting conditions that allow the first polymer component to be thermally decomposed and the ceramic compound particles to be linked to each other to form an ion conductor with a cross-linked structure. For example, the sintering can be performed at a temperature of 800°C to 1300°C, and more specifically, the sintering temperature may be 850°C or more, 900°C or more, or 950°C or more, or 1300°C or less, 1250°C or less, or 1200°C or less.

[0045] In the present invention, in step (S4), the ceramic ion conductor may be immersed in a solution containing a second polymer and a lithium salt, and cured to prepare a second composite body.

[0046] The second composite body contains the ceramic ion conductor, so that a composite solid electrolyte having improved ion conductivity can be produced.

[0047] The second polymer may be a polymer that has excellent solubility and dissociation degree of lithium salt, does not cause a side reaction with the ceramic compound when the second polymer and the lithium salt are mixed, and the polymer solution is easily impregnated into the ceramic ion conductor, making it easy to prepare a final composite solid electrolyte. Specific examples of the second polymer include polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate, PMMA), poly(4-styrenesulfonyl(trifluoromethylsulfonyl)imide, PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acryl amide), poly(acrylic acid), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, and the like. The binder may include one or more selected from the group consisting of acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol (amino-terminated PEG).

[0048] In the present invention, the lithium salt is contained in a dissociated state within the structure formed by the ceramic ion conductor, thereby improving the ionic conductivity of the composite solid electrolyte. Also, the lithium salt is mainly dissociated within the second polymer, thereby compensating for the loss of lithium ions generated from the ceramic compound particles during the high-temperature sintering process in step (S3).

[0049] The lithium salts include (CF3SO2)2NLi (lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.

[0050] The ceramic ion conductor prepared in step (S3) may be immersed in or coated with a solution containing a second polymer and a lithium salt, and then cured. The immersion or coating and curing may be repeated several times.

[0051] The curing in the step (S4) may be thermal curing or UV curing.

[0052] The UV curing is as described above.

[0053] The thermal curing step may produce a second composite body having ion conductivity by curing the ceramic ion conductor while immersing the ceramic ion conductor in a solution containing the second polymer and a lithium salt.

[0054] The thermal curing step may be performed at, but is not limited to, 50° C. to 150° C. For example, the thermal curing step may be performed at, but is not limited to, 50° C. to 150° C., 60° C. to 150° C., 70° C. to 150° C., 80° C. to 150° C., 90° C. to 150° C., 100° C. to 150° C., 50° C. to 140° C., 50° C. to 130° C., 50° C. to 120° C., 50° C. to 110° C., or 50° C. to 100° C. If the thermal curing step is performed below the above temperature range, the formation of the second composite may be incomplete, and if the thermal curing step is performed above the above temperature range, the preparation of the composite solid electrolyte may be difficult due to thermal decomposition of the second polymer and the lithium salt.

[0055] The molar ratio ([Li] / [G]) of the second polymer to the lithium ([Li]) of the lithium salt may be 0.1 to 0.5, specifically, 0.1 or more, 0.2 or more, or 0.3 or more, and 0.4 or less, or 0.5 or less. If the molar ratio ([Li] / [G]) is less than 0.1, the content of the lithium salt may decrease, and the ionic conductivity of the composite solid electrolyte may decrease. If the molar ratio ([Li] / [G]) is more than 0.5, the ionic conductivity may decrease due to the aggregation of lithium ions. Therefore, in the composite solid electrolyte according to the present invention, the second composite needs to have a composition of the second polymer and an appropriate amount of lithium salt.

[0056] Composite solid electrolyte for lithium secondary batteries The composite solid electrolyte for a lithium secondary battery according to the present invention includes a ceramic ion conductor including a ceramic compound; a second polymer; and a lithium salt, and the ceramic ion conductor may include a cross-linked structure including the ceramic compound.

[0057] Conventional composite solid electrolytes are manufactured by coating or dispersing a solution or slurry of a mixture of polymer and inorganic material on a substrate by a method such as solution casting, and then drying the coated solution or slurry. However, this method has a problem that the ionic conductivity of the solid electrolyte is not improved due to non-uniform dispersion and precipitation of inorganic material in the polymer solution.

[0058] To improve this, the present invention provides a composite solid electrolyte including a ceramic ion conductor having a cross-linked structure that forms an ion conduction path for lithium ions, a polymer, and a lithium salt. The ceramic ion conductor has ceramic compound particles uniformly dispersed therein, and can play a role in improving the ion conductivity of the composite solid electrolyte.

[0059] In one embodiment of the present invention, the ceramic ionic conductor may include a cross-linked structure that includes the ceramic compound.

[0060] The ceramic ion conductor may include a cross-linked structure formed by connecting the ceramic compound particles to each other, and the first polymer serves as a support to enable the ceramic compound particles to be connected to each other.

[0061] The ceramic ion conductor may serve to form an ion conduction path for lithium ions.

[0062] The specific method for producing the ceramic ion conductor is as described above.

[0063] The first polymer may include at least one selected from the group consisting of polyisocyanurate (PIR), epoxy, polyurethane, polyacrylate, and poly(methyl methacrylate) (PMMA).

[0064] In the polyacrylate, examples of the UV-curable acrylate monomer include hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), ethylene glycol diacrylate (EGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylated triacrylate (TMPEOTA), glycerol propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETA), and dipentaerythritol hexaacrylate (DPHA), but are not limited thereto. Any acrylate monomer commonly used in the art may be used without particular limitation.

[0065] The ceramic compound may be an oxide-based or phosphate-based solid electrolyte. The oxide-based or phosphate-based solid electrolyte may be a garnet-type lithium-lanthanum-zirconium oxide (LLZO, Li7La3Zr2O 12 ), perovskite-type lithium-lanthanum-titanium oxide (LLTO, Li 3x La 2 / 3-x TiO3), phosphate-based NASICON-type lithium-aluminum-titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO4)3), lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5The oxide- or phosphate-based solid electrolytes have a very high grain boundary resistance, and therefore require a sintering process at 1000°C or higher. This causes problems such as lithium volatilization at high temperatures, phase transition, and impurity phase formation. However, oxide- or phosphate-based solid electrolytes generally have a maximum sintering temperature of 10 -4 ~10 -3 It has an ionic conductivity of 100 S / cm, is stable in a high voltage region, is stable in air, and is easy to synthesize and handle. Therefore, the first polymer according to the present invention can be mixed with a different material to prepare a hybrid solid electrolyte, thereby making it possible to compensate for the shortcomings of each material.

[0066] In one embodiment of the present invention, the composite solid electrolyte for a lithium secondary battery may include a ceramic ion conductor; a second polymer, and a lithium salt.

[0067] The ceramic ion conductor is as described above.

[0068] The second polymer may be a polymer that has excellent solubility and dissociation degree of lithium salt, does not cause a side reaction with the ceramic compound when the second polymer and the lithium salt are mixed, and the polymer solution is easily impregnated into the ceramic ion conductor, making it easy to prepare a final composite solid electrolyte. Specific examples of the second polymer include polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate, PMMA), poly(4-styrenesulfonyl(trifluoromethylsulfonyl)imide, PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acryl amide), poly(acrylic acid), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, and the like. The binder may include one or more selected from the group consisting of acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol (amino-terminated PEG).

[0069] In the present invention, the lithium salt is contained in a dissociated state within the structure formed by the ceramic ion conductor, and can improve the ionic conductivity of the composite solid electrolyte.

[0070] The lithium salts include (CF3SO2)2NLi (lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.

[0071] The molar ratio ([Li] / [G]) of the second polymer to the lithium ([Li]) of the lithium salt may be 0.1 to 0.5, specifically, 0.1 or more, 0.2 or more, or 0.3 or more, and 0.4 or less, or 0.5 or less. If the molar ratio ([Li] / [G]) is less than 0.1, the content of the lithium salt may decrease, and the ionic conductivity of the composite solid electrolyte may decrease. If the molar ratio ([Li] / [G]) is more than 0.5, the ionic conductivity may decrease due to the aggregation of lithium ions. Therefore, in the composite solid electrolyte according to the present invention, the second composite needs to have a composition of the second polymer and an appropriate amount of lithium salt.

[0072] In the present invention, the composite solid electrolyte may be in the form of a free-standing film. The free-standing film refers to a film that can maintain a film shape by itself without a separate support at room temperature and pressure.

[0073] The free-standing film exhibits elasticity and minimizes brittleness, and has properties as a support that stably contains lithium ions, making it suitable for use as a composite solid electrolyte.

[0074] In the present invention, the ionic conductivity of the composite solid electrolyte is 10 -5 It may be S / cm or more.

[0075] Although the composite solid electrolyte is a solid electrolyte as described above, it exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, and can improve the performance of all-solid-state batteries.

[0076] all solid state battery The present invention also relates to an all-solid-state battery including the composite solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a composite solid electrolyte interposed between the negative electrode and the positive electrode, the composite solid electrolyte having the above-mentioned characteristics.

[0077] Specifically, the composite solid electrolyte contains a ceramic ion conductor and improves the ion conduction of lithium ions, making it suitable as an electrolyte for an all-solid-state battery.

[0078] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.

[0079] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.

[0080] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M'b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals; 1+y Mn 2-y Lithium manganese oxides such as LiMnO4 (where y is 0-0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7; and the chemical formula LiNi 1-y Ni-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y=0.01-0.3); chemical formula LiMn 2-y M y Examples of such compounds include, but are not limited to, lithium manganese composite oxides expressed as Li2Mn3MO8 (where M=Co, Ni, Fe, Cr, Zn, or Ta, and y=0.01-0.1) or Li2Mn3MO8 (where M=Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.

[0081] In addition, the positive electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.

[0082] The binder is a component that aids in bonding the positive electrode active material to the conductive material and the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polybutadiene ... The binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.

[0083] The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 1 wt% or more or 3 wt% or more, and 15 wt% or less or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, resulting in a decrease in battery capacity.

[0084] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon. Examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. These may be used alone or in combination of two or more kinds, but are not necessarily limited thereto.

[0085] The conductive material may be contained in an amount of 0.5 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the content of the conductive material may be 0.5 wt% or more or 1 wt% or more, and 20 wt% or less or 30 wt% or less. If the content of the conductive material is too small, such as less than 0.5 wt%, it may be difficult to expect an improvement in electrical conductivity or the electrochemical properties of the battery may be deteriorated, and if the content is too large, such as more than 30 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of including the conductive material in the positive electrode is not significantly limited, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.

[0086] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.

[0087] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.

[0088] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may include various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.

[0089] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, coating the composition on a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. In this case, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.

[0090] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.

[0091] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy.

[0092] The lithium ion (Li +The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0093] Preferably, the negative electrode active material is lithium metal, specifically, in the form of a lithium metal thin film or lithium metal powder.

[0094] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, or 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.

[0095] The binder is the same as that described above in the positive electrode active material layer.

[0096] The conductive material is as described above in the positive electrode active material layer.

[0097] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface.

[0098] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.

[0099] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0100] Specific examples of the device include, but are not limited to, power tools that are driven by a battery-type motor; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; power storage systems, etc. Preferred examples are shown below to aid in the understanding of the present invention. However, the following examples are merely illustrative of the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention, and such changes and modifications naturally fall within the scope of the accompanying claims.

[0101] Preferred examples are shown below to aid in understanding the present invention. The following examples are provided to facilitate understanding of the present invention, and the present invention is not limited thereto.

[0102] In the following examples and comparative examples, ceramic ion conductors containing polymers, ceramic compounds, etc. as shown in Table 1 below were produced, and composite solid electrolytes containing the same were produced.

[0103] [Table 1]

[0104] Example 1: Preparation of composite solid electrolyte (1) Preparation of the first complex A solution containing thiol-ene polyisocyanurate (PIR) and LLZO powder, a ceramic compound, was prepared. 1% by weight of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added as a photoinitiator to the solution. The weight ratio of PIR to LLZO was 1:2.

[0105] The solution was applied onto the substrate, SS foil, by bar coating, and then irradiated with ultraviolet (UV) light to harden it, inducing cross-linking of the PIR to produce a network-type composite.

[0106] (2) Manufacturing of ceramic ionic conductors The composite was separated from the substrate, and the temperature was raised from room temperature to 800°C at a rate of 1°C / min. Then, the composite was sintered at 800°C for 2 hours to pyrolyze the PIR components and sinter the remaining LLZO particles to produce a ceramic ion conductor.

[0107] (3) Manufacturing of composite solid electrolyte A solution containing PVA and LiTFSI was prepared (here, the molar ratio ([Li] / [O]) of “O” contained in PVA and “Li” contained in the lithium salt was 0.4), and the ceramic ion conductor was immersed in the prepared solution and then dried at room temperature for 12 hours. The resulting solution was then dried in a vacuum drying oven at 100° C. for 12 hours to completely remove the residual solvent, thereby preparing a composite solid electrolyte.

[0108] Example 2 A composite solid electrolyte was prepared in the same manner as in Example 1, except that LSTP was used instead of the ceramic compound LLZO.

[0109] Example 3 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the UV-curable polymer (PIR) and the ceramic compound (LLZO) was 1:10.

[0110] Example 4 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the UV-curable polymer (PIR) and the ceramic compound (LLZO) was 10:1.

[0111] Example 5 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the content of the photoinitiator was 0.1 wt %.

[0112] Example 6 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the content of the photoinitiator was 0.4 wt %.

[0113] Example 7 A composite solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the PVA and “Li” contained in the lithium salt was 0.08.

[0114] Example 8 A composite solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the PVA and “Li” contained in the lithium salt was 0.52.

[0115] Example 9 A composite solid electrolyte was prepared in the same manner as in Example 1, except that PEO was used instead of the polymeric PVA.

[0116] Example 10 A composite solid electrolyte was prepared in the same manner as in Example 1, except that PIR was used instead of the polymeric PVA.

[0117] Comparative Example 1 A composite solid electrolyte was produced in the same manner as in Example 1, except that no step after the sintering process was carried out after the preparation of the composite.

[0118] Comparative Example 2 A composite solid electrolyte was prepared in the same manner as in Comparative Example 2, except that after UV irradiation, the composite solid electrolyte was dried at 80° C. for 2 hours instead of being cured.

[0119] Experimental Example Experimental Example 1 The ionic conductivity of the film-type composite solid electrolyte prepared in the Examples and Comparative Examples was measured using a test tube with a thickness of 1.7671 cm 2 The composite solid electrolyte was punched out into a circular shape of a desired size, and the punched composite solid electrolyte was placed between two pieces of stainless steel (SS) to prepare a coin cell.

[0120] Resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. with an amplitude of 10 mV and a scan range of 500 kHz to 20 MHz, and then the ionic conductivity of the composite solid electrolyte was calculated using the following Equation 1.

[0121] [Formula 1]

number

[0122] In the above formula 1, σ i is the ionic conductivity (S / cm) of the composite solid electrolyte, R is the resistance (Ω) of the composite solid electrolyte measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the composite solid electrolyte, and A is the area (cm 2 )

[0123] The ionic conductivity of the composite solid electrolyte calculated using Equation 1, whether or not a hydrogel was formed, whether or not a freestanding film was formed, and the results of observing the appearance of the composite solid electrolyte are shown in Table 2. At this time, whether or not a freestanding film was formed (formed: O, not formed: X) and the appearance of the composite solid electrolyte were observed with the naked eye.

[0124] [Table 2]

[0125] As shown in Table 2, a solution in which the first polymer, which is a UV-curable polymer, and the ceramic compound are mixed in an appropriate weight ratio range is irradiated with UV light and cured, and then a sintering process is performed to form a ceramic ion conductor. It was confirmed that a composite solid electrolyte can be manufactured using the ceramic ion conductor manufactured through the above process (Examples 1 to 10).

[0126] In Examples 3 and 4, it was confirmed that a ceramic ion conductor was not formed when the weight ratio of the first polymer, which is a UV-curable polymer, to the ceramic compound was more than 1:10 or less than 10:1. Therefore, it was confirmed that in order to form a ceramic ion conductor according to the present invention, a proper range of the weight ratio of the first polymer to the ceramic compound must be satisfied.

[0127] In Examples 5 and 6, it was confirmed that a crosslinked film could not be produced unless the photoinitiator content was within the appropriate range.

[0128] In Examples 7 and 8, it was confirmed that when the concentrations of the second polymer and lithium salt during the preparation of the composite solid electrolyte were outside the range of 0.1 to 0.5, a film could not be formed, and this was not suitable for the preparation of the desired composite solid electrolyte.

[0129] Through Comparative Examples 1 and 2, it was found that even if a UV-curable polymer is simply used, a ceramic ion conductor or a crosslinked film cannot be formed unless the polymer is irradiated with UV light and cured or a sintering process is applied.

[0130] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it goes without saying that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below.

Claims

1. (S1) applying a composite solid electrolyte forming solution including a first polymer, which is a UV-curable polymer, and a ceramic compound onto a substrate to form a coating film; (S2) irradiating the coating film with ultraviolet (UV) light and then curing the coating film to produce a first composite material; (S3) sintering the first composite to produce a ceramic ion conductor; (S4) immersing the ceramic ion conductor in a solution containing a second polymer and a lithium salt and curing the solution to produce a second composite; A method for producing a composite solid electrolyte for lithium secondary batteries.

2. 2. The method of claim 1, wherein the first polymer comprises at least one selected from the group consisting of polyisocyanurate (PIR), epoxy, polyurethane, polyacrylate, and polymethyl methacrylate (PMMA).

3. 2. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 1, wherein the ceramic compound comprises at least one selected from the group consisting of lithium-lanthanum-zirconium oxide (LLZO), lithium-silicon-titanium phosphate (LSTP), lithium-lanthanum-titanium oxide (LLTO), lithium-aluminum-titanium phosphate (LATP), lithium-aluminum-germanium phosphate (LAGP) and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds.

4. 2. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 1, wherein the ceramic compound is present in an amount of 1 part by weight or more and less than 10 parts by weight relative to 1 part by weight of the first polymer.

5. The second polymer may be selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate) (PMMA), poly(4-styrenesulfonyl(trifluoromethylsulfonyl)imide (PSTFSI), polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, and poly(vinylpyrrolidone) (poly(vinyl 2. The method for producing the composite solid electrolyte for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of poly(N-pyrrolidone), poly(acrylamide), poly(acrylic acid), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.

6. The lithium salt is (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulphonyl)imide), LiTFSI, (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 The method for producing the composite solid electrolyte for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of:

7. 2. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 1, wherein a molar ratio of lithium ([Li]) of the lithium salt to a molar concentration ([G]) of the second polymer is 0.1 to 0.

5.

8. A composite solid electrolyte for a lithium secondary battery, comprising: a ceramic ion conductor comprising a ceramic compound; a second polymer; and a lithium salt.

9. 9. The composite solid electrolyte for a lithium secondary battery according to claim 8, wherein the ceramic compound comprises at least one selected from the group consisting of lithium-lanthanum-zirconium oxide (LLZO), lithium-silicon-titanium phosphate (LSTP), lithium-lanthanum-titanium oxide (LLTO), lithium-aluminum-titanium phosphate (LATP), lithium-aluminum-germanium phosphate (LAGP), and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds.

10. The second polymer may be selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate) (PMMA), poly(4-styrenesulfonyl(trifluoromethylsulfonyl)imide (PSTFSI), polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, and poly(vinylpyrrolidone) (poly(vinyl 9. The composite solid electrolyte for a lithium secondary battery according to claim 8, comprising at least one selected from the group consisting of poly(N-pyrrolidone), poly(acrylamide), poly(acrylic acid), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.

11. The lithium salts include LiTFSI (lithium bis(trifluoromethanesulphonyl)imide), LiFSI (lithium bis(fluorosulfonyl)imide), and LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi, (FSO 2 ) 2 9. The composite solid electrolyte for a lithium secondary battery according to claim 8, comprising at least one selected from the group consisting of NLi, lithium chloroborane, lithium lower aliphatic carboxylate, and lithium tetraphenylborate.

12. 9. The composite solid electrolyte for lithium secondary batteries according to claim 8, wherein the molar ratio of the lithium ([Li]) of the lithium salt to the molar concentration ([G]) of the second polymer is 0.1 to 0.

5.

13. The composite solid electrolyte for a lithium secondary battery according to claim 8, wherein the composite solid electrolyte is in the form of a freestanding film.

14. The ionic conductivity of the composite solid electrolyte is 1.0×10 -5 9. The composite solid electrolyte for a lithium secondary battery according to claim 8, having a specific surface area of ​​1.5 S / cm or more.

15. An all-solid-state battery comprising the composite solid electrolyte for a lithium secondary battery according to any one of claims 8 to 14.

Citation Information

Patent Citations

  • High-ionic-conductivity composite solid electrolyte and preparation method thereof

    CN110492170A

  • Polyelectrolytic element, polyelectrolytic element roll manufacturing method, and method of manufacturing polyelectrolytic element roll and battery

    JP2001256826A

  • Manufacturing method of solid electrolyte structure, manufacturing method of all-solid-state-cell, solid electrolyte structure, and all-solid-state-cell

    JP2009238739A

  • All-solid-state lithium-sulfur electrochemical cell and method for producing the same

    JP2016524803A

  • Composite solid electrolyte, protection negative electrode including the same, lithium battery, and method for manufacturing composite solid electrolyte

    JP2017191766A